2017
DOI: 10.1016/j.tra.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the transition towards Battery Electric Vehicles: A Multi-Level Perspective on drivers of, and barriers to, take up

Abstract: The Multi-Level Perspective (MLP) framework on transitions is used to interpret European electric vehicle take up and auto mobility transition. It finds that environmental and energy security pressures have created a favourable landscape 'push' for Battery Electric Vehicles (BEVs) that in turn has encouraged and facilitated serious commitment from some manufacturers. Yet BEVs, as a niche product seeking to disrupt an entrenched and established regime, face significant multi-level forces acting as barriers agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 71 publications
(117 reference statements)
1
65
0
1
Order By: Relevance
“…Second, and empirically, the critical lens of the study aims to force more justice aware research and policymaking related to EVs in the Nordic region (and beyond), so that vulnerabilities and risks can be mitigated, and losers minimized or compensated. The Nordic region has aggressive energy, transport and climate policies backed by welfare states with high taxes (Westholm and Lindahl 2012); high penetration rates for the adoption of renewable electricity and energy efficiency (International Energy Agency and Nordic Energy Research 2013, International Energy Agency andNordic Energy Research 2016;Sovacool 2017); and (most relevant for this study) high rates of adoption for EVs (Berkeley et al 2017). The International Energy Agency (2018) notes that across Denmark, Finland, Iceland, Norway, and Sweden, the total stock of EVs reached 250,000 cars at the end of 2017 and Energy injustice and electric mobility 5 accounted for 8% of the global total, the third-largest share after China and the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Second, and empirically, the critical lens of the study aims to force more justice aware research and policymaking related to EVs in the Nordic region (and beyond), so that vulnerabilities and risks can be mitigated, and losers minimized or compensated. The Nordic region has aggressive energy, transport and climate policies backed by welfare states with high taxes (Westholm and Lindahl 2012); high penetration rates for the adoption of renewable electricity and energy efficiency (International Energy Agency and Nordic Energy Research 2013, International Energy Agency andNordic Energy Research 2016;Sovacool 2017); and (most relevant for this study) high rates of adoption for EVs (Berkeley et al 2017). The International Energy Agency (2018) notes that across Denmark, Finland, Iceland, Norway, and Sweden, the total stock of EVs reached 250,000 cars at the end of 2017 and Energy injustice and electric mobility 5 accounted for 8% of the global total, the third-largest share after China and the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Vs have great potential to contribute to the decarbonization of society and help achieve national and international climate targets by reducing emissions of both the transport sector, which accounts for one-quarter of energy-related global greenhouse gas emissions, and the electricity sector, via better integration and utilization of renewable energy sources [1][2][3][4][5][6] . In turn, a growing stream of research has explored the social, political and market implications and barriers to EV diffusion and use 2,7,8 ; from taxation and policy incentives [9][10][11] , to consumer-focused studies [12][13][14] .…”
mentioning
confidence: 99%
“…They found that the relatively insignificant EV market share is partially due to limited driving range. Battery range concerns may be rooted in technology misconceptions about reliability (Berkeley et. al, 2017;Jin & Slowik, 2017).…”
Section: Range Constraints and Operationsmentioning
confidence: 99%
“…Singer 2016concluded that understanding how ZEVs can reduce environmental impacts and increase fuel savings influenced respondent ZEV opinions. In contrast, Berkeley et al (2017) questioned whether heightened environmental awareness leads to confidence in BEV emission reduction potential. They suggest that consumers with a high level of awareness could also be skeptical about the cleanliness of the electricity grid.…”
Section: Demographics and Zev Purchasing Behaviormentioning
confidence: 99%